APPLICATION OF PROBLEM-BASED LEARNING BASED ON ETHNOMATHEMATICS CANDI IJO TO IMPROVE MATHEMATICS LEARNING OUTCOMES ON FLAT BUILDINGS MATERIAL STUDENTS OF MTSN 9 BANTUL (Proceedings of the International Conference on Education, 2025)
The application of ethnomathematics-based problem-based learning model has been found to improve student engagement and mathematics learning outcomes. The study aims to improve students' mathematics learning outcomes through the application of problem-based learning model based on ethnomathematics of candi ijo in class VIII C MTsN 9 Bantul in the 2024/2025 academic year. This research is a class action research conducted in 2 cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were 30 students of class VIII C MTsN 9 Bantul in the 2024/2025 academic year. Research data were obtained through tests, interviews, and documentation. Data analysis used descriptive qualitative analysis techniques. Data validation using method triangulation techniques. The results showed that there was an increase in the learning outcomes of VIII C MTsN 9 Bantul students in the 2024/2025 academic year through the application of the problem-based learning model based on candi ijo ethnomathematics. The increase in learning outcomes is indicated by the increase in the average percentage achievement of math learning outcomes from 65.74% in the pre-cycle to 73.25% in cycle 1, further increasing to 80.15% in cycle 2. Based on these results, it can be concluded that there is an increase in student learning outcomes in mathematics, especially in flat building material through the application of the problem-based learning model based on candi ijo ethnomathematics.
Keywords: ethnomathematics; problem-based learning model; learning outcomes